Macroeconomic activities and stock prices in a South Pacific island economy - Puah, Chin Hong; Jayaraman, Tiru K. (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
This paper investigates whether there is any causal relationship between capital stock prices and macroeconomic activities in Fiji. The empirical results show that all the time series data are nonstationary and cointegrated with a single vector. All the explanatory variables have been found to contribute to the long-run equilibrium relationship. The estimation of the error-correction model further confirms that the stock price index is cointegrated with real economic activities in the long run, and it adjusts rather fast from short-run deviations towards longrun equilibrium level. Except for interest rate, real output, M2 and exchange rate do Granger cause stock prices in the short-run.